The targeting of T-helper cells and tumourcidal macrophages to a B-cell lymphoma using a PPD-monoclonal antibody heteroconjugate. - Montgomery, A M (1992)
This paper describes a T-cell targeting strategy based on the use of an antigen-monoclonal antibody heteroconjugate. A rat anti-idiotypic monoclonal antibody specific for a murine B-cell lymphoma was conjugated to the purified protein derivative (PPD) of tuberculin. This construct selectively delivered up to 4.5 x 10(4) molecules of PPD onto each tumour cell. Targeted PPD was internalized for endosomal processing and was presented in association with the I-A class II restriction element to PPD-reactive T-helper (Th) cells. Activated Th cells were demonstrated to proliferate and secrete significant levels of tumour necrosis factor (TNF). Such lymphokine secretion was observed at a PPD concentration as low as 1 ng/ml. Despite the secretion of TNF, the B-cell lymphoma was found to be resistant to autonomous Th-mediated cytotoxicity. Targeted Th cells did, however, activate tumourcidal macrophages that subsequently mediated significant tumour cytostasis. Based on this observation, it is proposed that the targeting system described may be exploited as the basis for a future immunotherapeutic strategy.